Characterisation of a germplasm collection of the tropical pasture legume Centrosema brasilianum in subhumid West Africa - Peters, M.; Kramer, H.; Tarawali, Shirley A.; Schultze-Kraft, Rainer (1998)
The available world collection consisting of 257 accessions of the tropical pasture legume Centrosema brasilianum (L.) Benth. was assessed between 1993 and 1995 in northern Nigeria to complement existing knowledge on the genetic diversity of this species and to identify accessions with high agronomic potential for subhumid west Africa. The excellent nutritive value and good dry matter productivity of C. brasilianum and its outstanding ability to remain green over extended dry periods confirmed its potential as an important forage resource, especially for the dry season, and indicated its possible role in soil conservation. Two distinct groups, comprising 10 and 11 accessions, were identified for further evaluation in short fallow and pasture systems, respectively. Accessions in the first group had a fast establishment, very high yields in the establishment year and good drought tolerance but yields were low to average in subsequent years. Accessions in the second group had sustained high yields under grazing, a high competitive ability and good drought tolerance.